2016
DOI: 10.1007/s11136-016-1270-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the psychometrics of a PROMIS item bank: self-efficacy for managing daily activities

Abstract: Purpose The aim of this study is to investigate the psychometrics of the Patient-Reported Outcomes Measurement Information System self-efficacy for managing daily activities item bank. Methods The item pool was field tested on a sample of 1087 participants via internet (n = 250) and in-clinic (n = 837) surveys. All participants reported having at least one chronic health condition. The 35 item pool was investigated for dimensionality (confirmatory factor analyses, CFA and exploratory factor analysis, EFA), i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 30 publications
(40 reference statements)
1
20
0
Order By: Relevance
“…Other studies have found negligible DIF of PROMIS items yet propose the value of examining DIF as a tool to implement assessments appropriately (e.g., Cook, Bamer, Amtmann, Molton, & Jensen, 2012; Coster et al, 2016; Hong et al, 2016). Moreover, similar effect sizes (pseudo R 2 = .001 to .003) have been associated with impactful DIF in other studies (Crane et al, 2007).…”
Section: Discussionmentioning
confidence: 95%
“…Other studies have found negligible DIF of PROMIS items yet propose the value of examining DIF as a tool to implement assessments appropriately (e.g., Cook, Bamer, Amtmann, Molton, & Jensen, 2012; Coster et al, 2016; Hong et al, 2016). Moreover, similar effect sizes (pseudo R 2 = .001 to .003) have been associated with impactful DIF in other studies (Crane et al, 2007).…”
Section: Discussionmentioning
confidence: 95%
“…[1, 30, 31, 38] Confirmatory factor analyses (CFA) were used to investigate the underlying structure (dimensionality) of the item bank using Mplus version 7.11. [39] Because the data was treated as ordered categorical, all model parameters were estimated using the weighted least square mean-and-variance adjusted (WLSMV) estimator and a one-factor solution.…”
Section: Methodsmentioning
confidence: 99%
“…The detailed psychometric results for one of the banks (Managing Daily Activities) have been previously published [38], but an overview of the findings from all the banks is presented here. Internal consistency of the five PROMIS Self-efficacy banks and short forms was high, with Cronbach’s alphas ranging from 0.96–0.97 for the full bank, 0.90–0.95 for the 8-item short forms, and 0.85–0.92 for the 4-item short forms.…”
Section: Methodsmentioning
confidence: 99%
“…2, the first box is called Falls Specific and contains six subdomains: (1) fall-related self-efficacy or fall selfefficacy, (2) fear of falling, (3) balance confidence, (4) consequences of falling, (5) perceived control over falling, and (6) perceived ability to manage falls [27][28][29]. A second box is called Self-efficacy of Managing Chronic Disease, a domain that in the future should be measured by the new PROMIS self-efficacy item banks including five subdomains: (1) self-efficacy of managing symptoms, (2) self-efficacy of managing emotions, (3) self-efficacy of managing daily activities, (4) self-efficacy of managing medications and treatments, and (5) self-efficacy of managing social interactions [30]. The third box is called Other Fall-related Self-efficacy and contains four constructs: (1) self-efficacy of physical activity, (2) self-efficacy of neighborhood barriers, (3) self-efficacy of gait, and (4) self-efficacy of mobility [27,31,32].…”
Section: Original Researchmentioning
confidence: 99%